Empowering University Educators for Contemporary Open and Networked Teaching - Nascimbeni, Fabio (Radical Solutions and Open Science. Lecture Notes in Educational Technology, 2020)
The chapter explores the competences that university educators should master in our increasingly digital, open and connected societies in order to fill their role effectively and responsibly. Starting from a brief analysis of the concepts of collaborative learning and open education, we analyse three teachers’ competencies frameworks, focusing on the digital, collaboration and openness aspects of contemporary teaching. We conclude that educators should not build radically new competences but should rather update their competences in line with emerging needs. Also, we notice that some additional competence areas should be developed by educators, if we want them to be able to bridge the work of students in formal and informal settings. We propose six competences areas in this sense: personal data management, capacity to leverage the open web, intercultural digital dialogues, critical view on media, digital ethical issues, accessibility. These areas are becoming increasingly important for educators to be able to critically engage learners in the core issues of our digital, networked and open societies, guiding them—in open and collaborative ways—towards solutions to the newly emerging problems of our times.
Keywords: open and networked teaching; higher education; teachers training; collaborative learning; teaching innovation; open education; Scopus(2)